The peyote road: religious freedom and the Native American Church - Maroukis, Thomas Constantine (The civilization of the American Indian series, 2010)
The origins and development of the peyote religion and the native -- American church -- Religious beliefs, ceremony, and ritual -- The assault on peyotism -- Expansion of peyotism -- Peyote art and music -- The struggle for constitutional protection